3D‐ultramicroscopy utilizing aspheric optics. Issue 1 (17th July 2013) - Saghafi, Saiedeh; Becker, Klaus; Hahn, Christian; Dodt, Hans‐Ulrich
Abstract Using a combination of achromatic aspheric optical elements and achromatic cylindrical lenses, we developed an improved laser light sheet generator for two‐side illumination ultramicroscopy. This light sheet generator has a much longer Rayleigh range, a more uniform spatial intensity distribution along x ‐, y ‐ and z‐axis, and reduced aberrations than the standard system consisting of a slit aperture and a single cylindrical lens, which is commonly used in light sheet microscopy. As there is no truncation of the beam by a slit aperture in our design the laser energy is used more efficiently. Applying this light sheet generator to ultramicroscopy of chemically cleared biological samples, such as Drosophila, dissected mouse hippocampi, and entire mouse brains, we achieved a markedly improved resolution of fine details. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)